Fungal phylogeny and plant functional traits structure plant–rhizosphere fungi networks in a subtropical forest. Issue 8 (5th May 2022) - Zhu, Chuchao; Wang, Zihui; Luo, Wenqi; Feng, Jiayi; Chen, Yongfa; He, Dong; Ellwood, M. D. Farnon; Chu, Chengjin; Li, Yuanzhi
Abstract : Although rhizosphere fungi are essential for plant survival and ecosystem functioning, little is known about the processes that structure plant–fungal association networks. In this study, we constructed association networks between 43 plant species and two groups of root‐associated fungi (mycorrhizal and pathogenic fungi; MF and PF, respectively) in a diverse subtropical forest. We then evaluated the modularity of plant–MF and plant–PF networks and linked them to the functional traits and phylogenies of both plants and fungi. We observed strong modularity in both plant–MF and plant–PF networks. Phylogenetically related fungi tended to emerge in the same modules. MF from distinct modules associated with plants with different specific root length and specific root area in plant–MF networks. PF from distinct modules associated with plants with different dark respiration rate and light compensation point in plant–PF networks. Plant affiliation to modules was explained by both plant traits and phylogeny (22% for plant–MF and 37% for plant–PF networks). In contrast, fungal affiliation to modules was explained by fungal phylogeny (16% for plant–MF and 29% for plant–PF networks). Our results elucidate the link between modularity in plant–root fungal networks and the functional traits and phylogeny of the plants and fungi. Our study highlights the importance of traits and phylogeny in governing root fungal community assembly from network perspective.